Multiculturalism versus assimilation: Attitudes towards immigrants in Western countries - Borooah K. Vani; Mangan John (International Journal of Economic Sciences and Applied Research, 2009)
A long standing area of debate in Western countries is that of the appropriate philosophy for facilitating large scale immigration; should immigrants preserve their traditions and culture while living in the host country (integration/multiculturalism) or should they assimilate themselves into the ways and manners of their hosts? The ways that nations go about resolving this issue goes to the heart of internal policy formulation on immigration but is also influential to the image that the country projects overseas. Countries are often labeled according to the official views of their Governments. For example, France might be classed as essentially assimilationist and Britain as multi-cultural, whereas the Netherlands and Germany might be seen as somewhere between the two, but how did these policy differences come about and do they accurately reflect the views of the majority of residents of the various countries? This paper addresses part of this issue by seeking to identify and analyse the characteristics of those people in Western countries who think that immigrants should assimilate culturally and how they differ from those who think that immigrants should preserve a separate cultural existence? By doing so, it seeks to explain why these inter-country differences in views exist and whether they are caused primarily by attribute effects (the composition of the population) or by coefficient effects (the strength of the views they hold). This study exploits a unique set of data provided by The Human Beliefs and Values Survey to identify and to estimate the strength of those factors which lead people to favour cultural integration over multiculturalism for immigrants. In doing so, it provides Governments with a snapshot of contemporary views on this increasingly important issue and how these views may shift as demographic characteristics alter.
Keywords: J61; F22; 330; immigrants; multiculturalism; assimilation; Western countries; logit; decomposition.